2005
DOI: 10.1631/jzus.2005.b1170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ST13 gene expression in colorectal cancer patients

Abstract: Abstract:We identified a novel gene ST13 from a subtractive cDNA library of normal intestinal mucosa in 1993, more studies showed that ST13 was a co-chaperone of Hsp70s. Recently we detected the ST13 gene expression in tumor tissue and adjacent normal tissue of the same colorectal cancer patient and investigated if the ST13 gene expression might have any prognostic value. Analysis was performed at molecular level by reverse transcription-PCR using real-time detection method. We measured two genes simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…( 30 ) Many previous studies by us have shown that ST13 gene expression levels are significantly decreased in primary colorectal cancers compared with adjacent mucosal tissues. ( 18,31 ) It raises the question of whether the low expression of ST13 is due to hypoxia in colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 30 ) Many previous studies by us have shown that ST13 gene expression levels are significantly decreased in primary colorectal cancers compared with adjacent mucosal tissues. ( 18,31 ) It raises the question of whether the low expression of ST13 is due to hypoxia in colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…( 15 ) The expression of ST13 was significantly lower in colorectal cancer than in adjacent normal colon mucosa. ( 15–18 ) Later studies proved that it encodes the approximately 41 kDa Hsp70‐interacting protein, a cofactor (cochaperone) of the 70‐kDa Hsc70 and Hsp70. ( 19–21 ) By collaborating with other positive cofactors such as Hsp40 and the Hsp70–Hsp90 organizing protein, or competing with negative cofactors such as Bcl2‐associated athanogen 1, Hsp70‐interacting protein may facilitate the chaperone function of Hsc70 and Hsp70 in protein folding and repair, and in controlling the activity of regulatory proteins such as steroid receptors and regulators of proliferation or apoptosis.…”
mentioning
confidence: 99%
“…Using Northern blot analysis and quantitative RT-PCR approaches, a decreased level of ST13 mRNA was observed in multiple colorectal cancer samples relative to that in their adjacent normal mucosa (Mo et al, 1996;1997a;1997b;Li and Zhang, 2000). However, the levels of ST13 mRNA showed no significant correlation with a tumor's differentiation grade, Dukes' stage, invasion depth, lymph node metastasis, or disease-specific survival (Dong et al, 2005). Similarly, recent in situ hybridization found that only 3 of 7 colon cancer tissues analyzed were positive for ST13 mRNA, whereas 7 of 7 normal colon tissues were positive (Wang et al, 2005).…”
Section: Physiological and Pathophysiological Rolementioning
confidence: 90%
“…In previous studies, we have proved that ST13 mRNA and protein levels were lower in colorectal cancer tissues compared with adjacent normal tissues (Mo et al, 1996;Zheng et al, 1997;Dong et al, 2005;Wang et al, 2005). Moreover, increased ST13 protein expression suppressed proliferation of colorectal cancer cells and induced apoptosis in colorectal cancer cell lines (Yang et al, 2008;Yu et al, 2009).…”
Section: Introductionmentioning
confidence: 89%